2011
DOI: 10.1128/jcm.02365-10
|View full text |Cite
|
Sign up to set email alerts
|

International External Quality Assurance for Laboratory Identification and Typing of Streptococcus agalactiae (Group B Streptococci)

Abstract: We report the results from the first international multicenter external quality assessment (EQA) studies for molecular and serological typing of group B streptococcus (GBS) strains as part of DEVANI (Design of a Vaccine against Neonatal Infections), a pan-European program. A questionnaire-based surveillance was undertaken among eight laboratories participating in DEVANI and six laboratories not participating in DEVANI from 13 countries in order to assess their current microbiological procedures for GBS screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 28 publications
(35 reference statements)
0
49
1
Order By: Relevance
“…Molecular Serotyping identification methods are attractive due to several advantages including being specific, their high discriminatory power, clear results, high reproducibility, simplicity and fast to perform, and great availability of equipment and required materials. Advanced molecular methods have capability of differentiating strains to many variable types (4,15,30).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular Serotyping identification methods are attractive due to several advantages including being specific, their high discriminatory power, clear results, high reproducibility, simplicity and fast to perform, and great availability of equipment and required materials. Advanced molecular methods have capability of differentiating strains to many variable types (4,15,30).…”
Section: Discussionmentioning
confidence: 99%
“…However, the results identify a problem with the serotype V and IX latex reagents (Statens Serum Institute) used for the agglutination tests (Table 1). Moreover, the accuracy of the results is highly dependent on experience (10), and the latex agglutination assay is less sensitive than the flow cytometric method as demonstrated by our observation that approximately one-half of the strains scored as nontypeable in this assay were found to express type-specific polysaccharides when examined by the flow cytometric method. The exact proportion of unselected isolates that would present this problem in clinical microbiology is not clear, as the strain collection examined in this study was enriched with strains that were difficult to type in other laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…Serological methods have limitations, as they may fail to type an isolate due to lack of or low expression of capsular polysaccharide under the experimental conditions. Furthermore, these methods are highly dependent on the quality of the antibodies used and on the experience of the laboratory (10). Therefore, capsular gene typing is an attractive alternative.…”
Section: S Treptococcus Agalactiae (Group B Streptococcus [Gbs]) Emergedmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of the serological assays used to detect GBS capsule polysaccharide can vary. These methods depend on the quality of the antibodies, the technical experience of the operator, and the expression of a detectable amount of capsule (53). A study by Kilian and coworkers (54) identified limitations associated with GBS latex agglutination serotyping.…”
Section: Discussionmentioning
confidence: 99%